La percezione di sé: coscienza, autocoscienza ed emozioni - Cimmino, Luigi (SocietàMutamentoPolitica, 2013)
Through a critical assessment of various concepts of self-consciousness and explaining the idea of con- sciousness as a property, the essay advances a conception of subjective self-reference basing on the peculiar temporality of intentional acts. By coming to that conclusion, topics typical of the philosophy of mind are enquired as the concept of intentionality, of sensory qualities and of the essence of emotion.